RECOGNITION OF COURAGE IN KARAN JOHAR'S MY NAME IS KHAN (2010):AN INDIVIDUAL PSYCHOLOGICAL APPROACH - HARIS, ARKIN (2011)
This study investigates the recognition of courage in Rizvan Khan reflected in My Name is Khan viewed from individual psychological approach. aims of this study are to analyze the structural elements of the movie analyze the movie based on individual psychological perspective. This study belongs to qualitative study. In this method, the writer uses of data sources, namely primary and secondary data sources. The primary sources and the object of the study is the movie itself, meanwhile secondary one is any literature related to this study for example reading resources related to the movie. The writer collects the data from primary and secondary data source in sort of document as evidence. The technique analyzing data is descriptive. Based on the analysis, the writer draws some conclusions as follows: Name is Khan tells about the major character as Rizvan Khan's courage. Second, every people has many ways to get recognition of courage. In My Khan, the major character, Rizvan Khan does some efforts to get recognition his courage that represents a case study of individual psychology. The last, major character's personality changes after he has goal to get recognition courage that his name is Khan. Finally, Islam is not similar to terrorism.